Implementation of an E-Commerce based Online Sales System at the Jaya Bersama Store in Padang - Monry, Muhammad Aviv (SAN Scientific, 2024)
This study aims to examine the implementation of an e-commerce-based online sales system at Toko Jaya Bersama, Padang. In today's digital era, e-commerce is an effective solution to increase sales and expand market reach. The system development method used is the waterfall development model. Data was collected through interviews, observations, and analysis of documents related to the online sales system implemented in the store. The results showed that the implementation of e-commerce in Toko Jaya Bersama has succeeded in increasing operational efficiency and store revenue. The online sales system implemented includes the creation of a store website, integration with digital payment platforms, and real-time inventory management. In addition, the implementation of digital marketing strategies through social media and SEO also contributes significantly in increasing store visibility and sales. However, there are some challenges faced in the process